The Effects of a Training Program on Development and Attitudes Towards Counseling for Prathom Sueksa Six Teachers in Schools Under the Jurisdiction of the Primary Educational Service Area Offices in the Lower Northeastern Region - Sitthisawatdiwut, Kamonluk; Suriyasasin, Srismorn; Chatsuppakul, Komphet; Wongyounoi, Somson (Ph.D. in Social Sciences Journal, 2019)
The purpose of this study were : (1) a training program for skills development and attitudes towards counseling for Prathom Sueksa Six. The researcher also examines (2) the effects of this program for skills development and attitudes towards counseling for Prathom Sueksa Six. The sample population consisted of 18 Prathom Sueksa Six. While the Mann-Whitney U test was used during the experiment and for the follow-up period. Findings are as follows: 1. The teachers in the experimental group prior to the commencement of the training program and after participating in the training program for the development of skills and attitudes towards counseling exhibited differences in test scores on skills and attitudes towards counseling at the statistically significant level of .01. 2. The teachers who participated in the training program and those who did not evinced differences in scores on skills and attitudes toward counseling at the statistically significant level of .01. 3. After participating in the training program and in the follow-up period, participant teachers did not display differences in skills and attitudes towards counseling. 4. The results of the observation of the skills of the teachers after participating in the training program are as follows: Eight of the nine ability in the aspect of attention skills at a good level. For all nine participants, ability in the aspects of listening skills, questioning skills, repeating skills, reflecting skills, interpreting skills, clarifying skills, informing skills, and summarizing skills was expressed at a very good level.